2017
DOI: 10.1128/aac.02531-16
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function of the PiuA and PirA Siderophore-Drug Receptors from Pseudomonas aeruginosa and Acinetobacter baumannii

Abstract: The outer membrane of Gram-negative bacteria presents an efficient barrier to the permeation of antimicrobial molecules. One strategy pursued to circumvent this obstacle is to hijack transport systems for essential nutrients, such as iron. BAL30072 and MC-1 are two monobactams conjugated to a dihydroxypyridone siderophore that are active against Pseudomonas aeruginosa and Acinetobacter baumannii. Here, we investigated the mechanism of action of these molecules in A. baumannii. We identified two novel TonB-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
109
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(112 citation statements)
references
References 71 publications
2
109
0
1
Order By: Relevance
“…WGS confirmed shortening of the proline‐rich region in Smlt0009 in KLTV (Figure a). TonB mutations are known to reduce susceptibility to siderophore‐conjugated antimicrobials in other species but have never previously been reported to affect β‐lactam susceptibility (Hassett et al, ; Moynie et al, ; Tomaras et al, ). Interestingly, S. maltophilia smlt0009 mutants do not have reduced susceptibility to the non‐siderophore‐conjugated parent lactivicin, LTV‐13 (Table ), even though this γ‐lactam is structurally related to the β‐lactams (Starr et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…WGS confirmed shortening of the proline‐rich region in Smlt0009 in KLTV (Figure a). TonB mutations are known to reduce susceptibility to siderophore‐conjugated antimicrobials in other species but have never previously been reported to affect β‐lactam susceptibility (Hassett et al, ; Moynie et al, ; Tomaras et al, ). Interestingly, S. maltophilia smlt0009 mutants do not have reduced susceptibility to the non‐siderophore‐conjugated parent lactivicin, LTV‐13 (Table ), even though this γ‐lactam is structurally related to the β‐lactams (Starr et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…in KLTV (Figure 2a). TonB mutations are known to reduce susceptibility to siderophore-conjugated antimicrobials in other species but have never previously been reported to affect β-lactam susceptibility (Hassett et al, 1996;Moynie et al, 2017;Tomaras et al, 2013).…”
Section: Wgs Confirmed Shortening Of the Proline-rich Region In Smlt0009mentioning
confidence: 99%
“…In this study, we show that while Fiu and its homologues PiuA and PiuD function in the import of catechol-siderophores [25,30], they are evolutionarily distinct from the well-studied catecholate siderophore transporters FepA/PfeA and Cir. In order to investigate the substrate import mechanism of the Fiu/Piu TBDT subgroup, we solved the crystal structure of Fiu.…”
Section: Introductionmentioning
confidence: 77%
“…To resolve this question, we performed phylogenetic analysis on these transporters in the context of a panel of diverse TBDTs of known structure and/or function. This analysis revealed that while Cir and FepA belong to the same clade of our TBDT phylogram, Fiu belongs to a distal clade with the TBDTs PiuA and PiuD that also mediate catecholate transport [30,33] ( Figure 1A). Wider analysis of this Fiu/Piu clade, identified by HMMER search reveals that related sequences are widespread in proteobacteria ( Figure S1, Table S1, Table S2).…”
Section: Fiu Is a Member Of A Distinct Clade Of Iron-catecholate Tranmentioning
confidence: 83%
See 1 more Smart Citation